Social sukuk: a new mechanism to fund social services / Saadiah Mohamad … [et al.] - Mohamad, Saadiah; Othman, Jaizah; Lehner, Othmar; Muda, Ruhaini (Universiti Teknologi MARA Selangor, 2017)
While the premise of Islamic finance embraces the principles of maqasid al-shariah and risk sharing with claims to social justice and welfare, the direct impact of the modern Islamic finance industry and its contribution to the social sector has been limited. This paper examines the claim among critics that there is an inherent weakness of the present day Islamic banking and finance in terms of its underdeveloped social sector and argues for the need for new models that will enhance a proliferation of shariah compliant financial products for solutions in the social sector. The paper examines the emergence in Social finance of social bonds as new financing tools targeting on social needs and problems that otherwise would not be tackled. This paper discusses the benefits of structuring such a shariah compliant product and makes recommendations for structuring this new asset class referred to in this paper as social sukuk.